2022
DOI: 10.17582/journal.aavs/2022/10.8.1718.1724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Microalgae Supplementation on Mammals’ Production and Health

Abstract: Effects of feeding green microalgae and Nigella sativa on productive performance and metabolic profile of Boer goats during peripartum period in subtropics. Fresen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Higher levels of AST can be a clue of liver damage, especially when paralleled with increased ALT (Pagana and Pagana, 2006). Moreover, the AST levels reported in the present study fall well within the normal bovine range (Aiello and Moses, 2019;Al-Mufarji et al, 2022).…”
Section: Biochemical Parameterssupporting
confidence: 84%
See 2 more Smart Citations
“…Higher levels of AST can be a clue of liver damage, especially when paralleled with increased ALT (Pagana and Pagana, 2006). Moreover, the AST levels reported in the present study fall well within the normal bovine range (Aiello and Moses, 2019;Al-Mufarji et al, 2022).…”
Section: Biochemical Parameterssupporting
confidence: 84%
“…subtilis and green microalgae supplementation to bulls improved the hematological and immunological parameters (Fig 1). Other studies concluded that hematological profile showed an insignificant change between different groups (Justine and Oluwatosin, 2008;Al-Mufarji et al, 2022). This indicated the improved health status of the supplemented beef bulls.…”
Section: Blood Parametersmentioning
confidence: 90%
See 1 more Smart Citation
“…It is classified into nutrient and nonnutrient supplement and it is given at less than one percent level of the compounded feeds (Mohammed and Attaai et al, 2011;Senosy et al, 2017Senosy et al, , 2018Halmemies-Beauc het-Filleau et al ., 2018;Mohammed and Al-Suwaiegh, 2023). It is given to ruminant and non-ruminant animals for different purposes including changes in feed intake and rumen micro-organisms, nutrient digestibility and body weight gain (Ali et al, 2021;Al-Mufarji et al, 2022 a,b,c), ovarian follicle development and the resulting oocyte and embryo quality (Mohammed, 2018;Mohammed and Farghaly et al, 2018) in addition to treatment or alleviate dysfunctions (Mohammed et al, 2012;Mohammed, 2019;Mohammed and Al-Hozab, 2020;Ali et al, 2021;Al Masruri et al, 2022c). The beneficial components of supplements includes proteins, polysaccharides, lipids, pigments, vitamins, minerals and other active substances (Fig 1).…”
Section: Introductionmentioning
confidence: 99%
“…Different factors modify milk yield and composition [8][9][10]. Feeding strategies can be used to modify milk yield and composition as lipid supplementation [11,12].…”
Section: Introductionmentioning
confidence: 99%